Proceedings of International Solid State Sensors and Actuators Conference (Transducers '97)
DOI: 10.1109/sensor.1997.635470
|View full text |Cite
|
Sign up to set email alerts
|

A simple ionizing radiation spectrometer/dosimeter based on radiation sensing field effect transistors (RadFETs)

Abstract: SummaryThis paper reports on the processing steps in a silicon foundry leading to improved performance of the Radiation Sensing Field Effect Transistor @&ET) and the use of multiple RadFETs in a handheld, battery operated, combination spectrometer/dosimeter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…This creates an irreversible shift in the FET's threshold voltage. Sandia has microfabricated miniature RadFETs [ 17 ]. Sensitivities depend in part upon fabrication structure and range from 0.01 to 5 mV per rad.…”
Section: Sensor Technologies For Environmental Monitoringmentioning
confidence: 99%
“…This creates an irreversible shift in the FET's threshold voltage. Sandia has microfabricated miniature RadFETs [ 17 ]. Sensitivities depend in part upon fabrication structure and range from 0.01 to 5 mV per rad.…”
Section: Sensor Technologies For Environmental Monitoringmentioning
confidence: 99%
“…This creates an irreversible shift in the FET's threshold voltage. Sandia has microfabricated miniature RadFETs (Moreno, 1997). Sensitivities depend in part upon fabrication structure, and range from 0.01 to 5 mV per rad.…”
Section: Radfet (Radiation-field Effect Transistor)mentioning
confidence: 99%
“…The influence of ionizing radiation (electrons, X-rays, γ-rays, protons and heavy ions) on devices based on the metal-insulator-semiconductor structures (MIS-capacitors and field-effect transistors called as MISFETs) are being studied since 1960' years (e.g., [1,2]). It was found that the general dose radiation effect is the irreversible change during irradiation of effective charge Qe, summarized effective charges Qt in an insulator and Qs in insulator-semiconductor interface [3,4]. This effect results in the deformations of MIS-capacitors' C-V characteristics and MISFETs' I-V characteristics (CVC), what are physical basics of the MIS-based dosimeters of ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%
“…MISFET-based sensors of the total ionizing dose D (TID) have been studied by many investigators [4][5][6][7][8]. Found that radiation sensitivity of sensors depend on electrical modes, structural and technological parameters of MISFET.…”
Section: Introductionmentioning
confidence: 99%